Competition between Airports in Krakow and Katowice as an Element of Development of Regions - Tłoczyński , Dariusz (Studia Oeconomica Posnaniensia, 2016)
The main topic of this paper is competition between airports. It is important from the point of view of the passenger and the air carrier. The combination of expectations of passengers and carriers is an important element for the functionality of the airports in a competitive area. Airports compete for passengers, air carriers, and an available time of flight operations. A classic case of competition is the airports in Cracow and Katowice. The main aim of this article is to analyze the impact of the instruments of competition between airports in Cracow and Katowice. The author performed market research in the analyzed airports and used secondary data. The main method used in the process of achieving the objective was analyzing comparative literature, analyzing source documents and heuristic analysis, and also the segregating and grouping of data obtained. The main instrument of competition is to offer carriers impact area airports and functioning system of airports links. Less important for the development of competition is having business units located in the vicinity of airports. Competition between airports contribute to the economic development of cities and regions. For this purpose, local actors and ports should work together. The development of airports is dependent on the development of the economy (shown in the accessibility factor), and is associated with investments airports and near-airports, which in turn leads to the development of the region.